Questioning North Korea’s digraphic inflection point: Kim Il Sung’s 1964 and 1966 conversations with linguists reconsidered - Strnad, William (Scripta Neophilologica Posnaniensia, 2021)
Kim Il Sung’s 1964 and 1966 conversations with linguists are appropriately deemed important as the establishment of the North’s “cultured language” as a standard, as well as guidance related to language purification and script. In the analysis of inflection point related to language planning and policy in the North, is the often guidance on re-enshrinement of teaching “Chinese characters” (hanja) in North Korean education. Clearly this was official pronouncement of functional, synchronic digraphia, which has been preserved and operationalized down to the present. Scholarship on these conversations, amounting to policy guidance, attribute the shift in policy related to script as an inflection point. The author of this article concurs with its importance, but with respect to digraphia in the North, the conversations related to hanja instruction served as a confirmation for what was a broad trend in North Korean language planning during the years 1953-1964, a language planning and policy fait accompli, diminishing the portrayal of the conversations as a digraphic inflection point in North Korea.